1994
DOI: 10.1111/j.1365-3059.1994.tb02705.x
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of MAV‐type barley yellow dwarf virus on wheat in the Garhwal Hills in India

Abstract: A serious outbreak of barley yellow dwarf luteovirus (BYDV, MAV-type) on wheat in the Garhwal Hills, Central Himalayas, India is reported. This is the first conclusive evidence based on serology for the presence of M AV-BYDV in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In recent years, BYDV GAV-caused wheat yellow dwarf disease has observed throughout the northern and north-western regions of China. It was reported that outbreak of BYDV in field often coincided with a high population of viruliferous aphid vectors on the overwintered host plants during the most susceptible stage of the wheat crops and the changes in cultivation practices [ 11 ]. BYDV was shown to accumulate in phloem cells and BYDV viroplasm, virion aggregates and BYDV specific tubular structures were observed in both infected plant and aphid cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, BYDV GAV-caused wheat yellow dwarf disease has observed throughout the northern and north-western regions of China. It was reported that outbreak of BYDV in field often coincided with a high population of viruliferous aphid vectors on the overwintered host plants during the most susceptible stage of the wheat crops and the changes in cultivation practices [ 11 ]. BYDV was shown to accumulate in phloem cells and BYDV viroplasm, virion aggregates and BYDV specific tubular structures were observed in both infected plant and aphid cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%